Convergent exaptation and adaptation in solitary island lizards - Poe, Steven (The Royal Society, 2007)
Independent evolutionary lineages often display similar characteristics in comparable environments. Three kinds of historical hypotheses could explain this convergence. The first is adaptive and evolutionary: nonrandom patterns may result from analogous evolutionary responses to shared conditions. The second explanation is exaptive and ecological: species may be filtered by their suitability for a particular type of environment. The third potential explanation is a null hypothesis of random colonization from a historically nonrandom source pool. Here we demonstrate that both exaptation and adaptation have produced convergent similarity in different size-related characters of solitary island lizards. Large sexual size dimorphism results from adaptive response to solitary existence; uniform, intermediate size results from ecological filtering of potential colonizers. These results demonstrate the existence of deterministic exaptive convergence and suggest that convergent phenomena may require historical explanations that are ecological as well as evolutionary.